Quinine ingestion during the latter stages of a 3,000-m time trial fails to improve cycling performance - Etxebarria, N.; Clark, B.; Ross, M. L.; Hui, T.; Goecke, R.; Rattray, B.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
The ingestion of quinine, a bitter tastant, improves short-term (30 s) cycling performance, but it is unclear whether this effect can be integrated into the last effort of a longer race. The purpose of this study was to determine whether midtrial quinine ingestion improves 3,000-m cycling time-trial (TT) performance. Following three familiarization TTs, 12 well-trained male cyclists (mean ± SD: mass = 76.6 ± 9.2 kg, maximal aerobic power = 390 ± 50 W, maximal oxygen uptake = 4.7 ± 0.6 L/min) performed four experimental 3,000-m TTs on consecutive days. This double-blind, crossover design study had four randomized and counterbalanced conditions: (a) Quinine 1 (25-ml solution, 2 mM of quinine); (b) Quinine 2, replicate of Quinine 1; (c) a 25-ml sweet-tasting no-carbohydrate solution (Placebo); and (d) 25 ml of water (Control) consumed at the 1,850-m point of the TT. The participants completed a series of perceptual scales at the start and completion of all TTs, and the power output was monitored continuously throughout all trials. The power output for the last 1,000 m for all four conditions was similar: mean ± SD: Quinine 1 = 360 ± 63 W, Quinine 2 = 367 ± 63 W, Placebo = 364 ± 64 W, and Control = 367 ± 58 W. There were also no differences in the 3,000-m TT power output between conditions. The small perceptual differences between trials at specific 150-m splits were not explained by quinine intake. Ingesting 2 mM of quinine during the last stage of a 3,000-m TT did not improve cycling performance.